The power of prints: the legacy of William M. Ivins and A. Hyatt - Van Camp, A (Burlington Magazine Publications, 2016)
Review of The Power of Prints: The Legacy of William M. Ivins and A. Hyatt Mayor. By Freyda Spira with Peter Parshall. 192 pp. incl. 169 col. ills. (The Metropolitan Museum of Art, New York, 2016), £25. ISBN 978-158839-585-6